The formation of holistic students: what are the roles of lecturers in institutes of higher learning? - Suhid, Asmawati; Jusoh, Rosnani; Bakar, Ab. Rahim; Mamat, Rohana (University Publications, 2014)
Students are individuals who will carry on the tasks and responsibilities in developing the community and country. Therefore, they should be developed in a balanced and integrated as well as be equipped in all aspects including spiritual and character aspects. Hence, the inculcation of moral values cannot be separated from the teaching and learning process. In other words, the task and responsibility of an educator is not only imparting knowledge and skills among the students but also inculcate moral values in them. In the current era of globalisation, the younger generation is seen to be easily influenced and trapped in social problems and moral decay. This situation worries many parties and if not addressed effectively will create worse problems that inteferes with the harmony of the community and country. This study was carried out to determine the extent to which lecturers inculcate moral values among the students who are important assets for the nation. Students from one of the Public Higher Learning Institution are involved in this study. The findings showed that lecturers often inculcate moral values in their teaching (highest mean = 3.60). Besides discussing the results of the study, the researcher also put forward opinions and suggestions to strengthen the efforts of moral values inculcation and holistically shape excellent students.